Teaming With a Synthetic Teammate: Insights into Human-Autonomy Teaming. (March 2018) - McNeese, Nathan J.; Demir, Mustafa; Cooke, Nancy J.; Myers, Christopher
Objective: Three different team configurations are compared with the goal of better understanding human-autonomy teaming (HAT). Background: Although an extensive literature on human-automation interaction exists, much less is known about HAT in which humans and autonomous agents interact as coordinated units. Further research must be conducted to better understand how all-human teams compare to HAT. Methods: In an unmanned aerial system (UAS) context, a comparison was made among three types of three-member teams: (1) synthetic teams in which the pilot role is assigned to a synthetic teammate, (2) control teams in which the pilot was an inexperienced human, and (3) experimenter teams in which an experimenter served as an experienced pilot. Ten of each type of team participated. Measures of team performance, target processing efficiency, team situation awareness, and team verbal behaviors were analyzed. Results: Synthetic teams performed as well at the mission level as control (all human) teams but processed targets less efficiently. Experimenter teams performed better across all other measures compared to control and synthetic teams. Conclusion: Though there is potential for a synthetic agent to function as a full-fledged teammate, further advances in autonomy are needed to improve team-level dynamics in HAT teams. Application: This research contributes to our understanding of how to make autonomy a good team player.